Impact of non-pulmonary visceral metastases in the prognosis and practice of metastatic testicular germ cell tumors - Lorena Rossi; Filippo Martignano; Valentina Gallà; Antonio Maugeri; Giuseppe Schepisi (Oncology Reviews, 2016)
Non-pulmonary visceral metastases, in bones, brain and liver, represent nearly the 10% of metastatic sites of advanced germ cell tumors and are associated with poor prognosis. This review article summarizes major evidences on the impact of different visceral sites on the prognosis, treatment and clinical outcome of patients with germ cell tumors. The clinic-biological mechanisms by which these metastatic sites are associated with poor clinical outcome remain unclear. The multimodality treatment showed a potential better survival, in particular in patients with relapsed disease. Patients with advanced germ cell tumors with visceral metastases should be referred to centers with high expertise in the clinical management of such disease.